Routledge Companion to Media Anthropology - Costa, Elisabetta; Lange, Patricia G.; Haynes, Nell; Sinanan, Jolynna (Taylor & Francis, 2023)
The Routledge Companion to Media Anthropology provides a broad overview of the widening and flourishing area of media anthropology, and outlines key themes, debates, and emerging directions. The Routledge Companion to Media Anthropology draws together the work of scholars from across the globe, with rich ethnographic studies that address a wide range of media practices and forms. Comprising 41 chapters by a team of international contributors, the Companion is divided into three parts: Histories Approaches Thematic Considerations. The chapters offer wide-ranging explorations of how forms of mediation influence communication, social relationships, cultural practices, participation, and social change, as well as production and access to information and knowledge. This volume considers new developments, and highlights the ways in which anthropology can contribute to the study of the human condition and the social processes in which media are entangled. This is an indispensable teaching resource for advanced undergraduate and postgraduate students and an essential text for scholars working across the areas that media anthropology engages with, including anthropology, sociology, media and cultural studies, internet and communication studies, and science and technology studies.